Performance indicators for collaborative networks based on collaboration benefits - Camarinha-Matos, Luis M. (2020)
Collaborative networks are typically assumed to bring clear benefits and competitive advantage to the participating members. However, the identification and characterisation of objective and measurable collaboration benefits is an important element for the wide adoption of this paradigm. Departing from a brief categorisation of the intuitive advantages of collaboration, this paper introduces an approach for the analysis of benefits in collaborative processes, introducing a number of performance indicators. The potential application of the indicators derived from this analysis is then discussed in the context of a virtual organisation’s breeding environment. Finally, experimental results based on data from two existing collaborative networks are presented and discussed.